Perancangan Aplikasi Duplicate Image Scanner Menerapkan Algoritma MD5 - Gaberia Sanchia Melati BR Lumbantoruan (Journal of Computing and Informatics Research, 2022)
Currently we are in the era of the digital world, there are lots of equipment that have tools to record photos in the form of cameras found on smartphones. The weakness of smartphones is the small storage space, so users must be good at managing files stored on the smartphone. There are so many applications in smartphones that provide facilities for sharing images. This of course will greatly burden the storage space of the smartphone because it stores image files which are generally large in size, especially if the image files are the same or duplicate, of course it is very burdensome for storage space. It will be very difficult to distinguish an image file without looking at the contents of the image file. So if you want to distinguish one image file from another, the user must see the contents of the image file and this will certainly be very difficult. For that we need a method that can be used to identify the same image file or duplicate image files so that a decision can be made to delete the duplicate document files so as to save storage space. In cryptography there is a hash function which is a one-way function that can generate the identity of a file, where if the image file contains the same content, it will produce the same hash value. It can be used to identify the same or duplicate image files. In the hash function there is the MD5 method or Message Digest 5 which is one of the hashing algorithms that is often used to encrypt data with a length of 128 bits. By applying this algorithm to the file scanner application, the results of the image file search are grouped based on the same hash value and users can make it easier and faster for users to delete duplicate image files without having to open and view the contents of the file